The Identity Dilemma : Social Movements and Collective Identity - Jasper, James M., 1957-; McGarry, Aidan (Book collections on Project MUSE., 2015)
"Collective identities are politically necessary, or at least useful, as banners for recruiting others and engaging opponents and the state. However, not every member fits or accepts the label in the same way or to the same degree. The Identity Dilemma provides eight diverse case studies of social movements to show the benefits, risks, and tradeoffs when a group develops a strong sense of collective identity. The editors and contributors to this pathbreaking volume examine how collective identities can provide powerful advantages but also generate conflicts. The various chapters help to develop our understanding of collective identity from how strategic identities are developed for protest groups to how stigmatized groups negotiate identity dilemmas. Ultimately, The Identity Dilemma contributes a new strategic approach to understanding social movements that highlights the choices and tensions that groups inevitably face in articulating their ideas and interests. Contributors include: Marian Barnes, Cristina Flesher Fominaya, Umut Korkut, Elzbieta Korolczuk, John Nagle, Clare Saunders, Neil Stammers, Marisa Tramontano, Huub Van Baar, and the editors."--